Digital compositing for film and video - Wright, Steve 1947- (Focal Press visual effects and animation series., 2010)
Addresses the problems and difficult choices that professional compositors face on a daily basis. The reader is presented with tips, techniques, and solutions for dealing with badly shot elements, color artifacts, mismatched lighting and other commonly faced compositing obstacles. Practical, in-depth lessons are featured for bluescreen matte extraction, despill operations, compositing operations, as well as color-corrections. --from publisher description.